Hubungan Shift Kerja dan Kebisingan dengan Stres Kerja Pada Karyawan Bagian Produksi Gilingan PT. Riau Crumb Rubber Factory Pekanbaru - Riri Juliyati; Zulfan Saam; Nopriadi Nopriadi (Universitas Riau, 2014)
This research aims to analyze the correlation between shift work and noise withwork stress of the workers in milling production division of PT . Riau Crumb Rubber Factory.This research is an observational analytic with cross sectional approach. The population ofthis study consists of 125 workers in milling production. With purposive sampling techniqueand using predetermined criteria obtained a total sample of 60 people. The data werecollected using work stress scale and the measurement noise by using a sound level meter andanalyzed with bivariate using the chi square test. The results showed that there was asignificant correlation between work shifts with work stress with p value (0.000) < α ( 0.05 ).Employees who work on the night shift tend to have a high work stress when compared withemployees working on the morning shift and afternoon . There is a significant correlationbetween the level of noise with work stress with p value (0.000) < α ( 0.05 ). The higher thenoise level the higher work stress.